Development of an auditing framework by integrating ISO 9001 principles within auditing. Issue 2 (19th November 2019) - Abuazza, Omran Ahmad; Labib, Ashraf; Savage, Barbara M.
Abstract : Purpose: The purpose of this paper is to develop an auditing framework which would assist the organizations that experience difficulties with the current ISO 9001 quality audits to achieve their planned objectives with regard to their auditing of conformance, performance, risk management (RM) and improvement collectively. Design/methodology/approach: A literature review was conducted to develop a conceptual audit framework (CAF). Subsequently, a preliminary audit framework (PAF) was developed. It includes the questions that are based on the CAF and connected with the complaints of the concerned organization. This PAF was thoroughly tested and validated by performing 11 internal audits, 2 management reviews (MR) and 3 workshops. Findings: Applying this PAF indicated that in order to help organizations to audit their performance, RM and improvement collectively, they need to: change their audit approach from ISO elements to ISO principles, integrate the tools that are related to ISO 9001 Principles within the audit's phases, perform pre-audits in the form of self-auditing, induce auditors to learn all tools to determine the ideal tools for particular situation, audit each department in combination with its internal customer, involve their auditors in problem solving, perform MR prior to closing the audit and analyze the results of audits with their causes by using one of the appropriate qualitative methods, such as analysis by themes. Finally, an auditing framework was developed to meet these needs. It includes the PAF's questions that led to the discovery of chronic and systematic audit findings. It enhances any ISO 9001 Quality Auditing Questionnaires Checklist. Originality/value: This study enhances the role of auditors to include risk identification, problem solving and data analysis by development of an auditing framework that is based on ISO 9001 Principles rather than clauses.